Exploring arid horticulture for nutritional security - Dutt, Som (Indian Horticulture, 2019)
It is a matter of great satisfaction for the country and more specifically to the farming community of the country that the total foodgrain production has already gone beyond 275 million tonnes during the last year. It is further important that for the first time the total horticultural production has also surpassed the total food grain production and reached to the tune of 305 million tonnes which is around 30 million metric tonnes more than the total food grain production in the country. Several times the quality of horticultural produce is also not meeting out the demands of the world standards fixed by different importing countries. With the adoption of modern technologies and high-yielding disease tolerant varieties, India has the capability to enhance the productivity and quality much more in comparison to the present productivity and quality in most of the horticultural crops. The Editor (Indian Horticulture) interacted with Dr Balraj Singh, Vice-Chancellor, Agriculture University, Jodhpur, Rajasthan. The excerpts are furnished herewith: